INSTITUTIONAL SUPPORT FOR THE IMPLEMENTATION OF THE STATE POLICY OF COMBATANTS’ SOCIAL PROTECTION - Hordiienko, Yevheniya (Pressing Problems of Public Administration, 2021)
The state policy on social protection of veterans, namely combatants is now implemented in the context of administrative and political reform and institutional transformations. Institutional changes in Ukraine involve the creation of new or reorganization (improvement) of existing institutions, the transformation of organizational and personnel activities of institutions, as well as the establishment of interaction between them. Thus, the purpose of the article is to analyze the institutional support for the implementation of the state policy of veterans’ social protection. Given the limited volume of the study, we will consider institutional support as a set of institutions that ensure the implementation of the state policy of veterans’ social protection. State policy is implemented at three levels (local, regional, national), according to which the author proposes to structure the main institutions of veterans’ social protection. The local level implies the implementation of their own self-governing and state-delegated powers for the veterans ‘ social protection by local government bodies (hereinafter referred to as LGB and local executive bodies. At the regional level, state policy is implemented by LGB of the regional level (regional councils), territorial executive bodies (regional state administrations, regional public services, centers, etc.), civil society groups and associations that protect the rights on veterans’ social protection at the oblast level, region. At the national level, the state policy and mechanisms of its implementation are formed, legislative documents are adopted, norms and standards are established, the order, procedures and regulations for financing budgetary programs of veterans’ social protection are determined. Currently, the state policy of veterans’ social protection is implemented by a large number of institutions and acts as a set of measures that demonstrate the Government’s response to the situation that arises under the influence of political factors. Since 2018 the Ministry of Veterans Affairs has become the main central body of executive power, which ensures the formation and implementation of the state policy of veterans’ social protection. Civil society institutions (public organizations, unions, associations, charitable foundations, etc.) also function at all levels. In the context of modernization of institutional support, the leading issue is the improvement of the legislative framework, the establishment of interaction between public authorities, local government bodies and civil society institutions. In our opinion, the state should direct its actions towards further transformation of existing institutions that will meet modern challenges.